IMPLEMENTASI PEMBELAJARAN CATUR GURU DALAM MEMBENTUK KARAKTER SISWA DI SMP NEGERI 1 TAMPAKSIRING - Dian Padmawati, Ni Kadek (UHN IGB Sugriwa Denpasar, 2024)
ABSTRACT Education is the key word for improving the welfare and dignity of the nation. The Catur Guru teaching is a teaching that focuses on students' behavior towards teachers, be they Rupaka Teachers, Recitation Teachers, Wisesa Teachers, and Swadyaya Teachers. From this background, we formulated several problems that we wanted to solve, including: (1) How is the implementation of teacher chess learning in shaping student character at SMP Negeri 1 Tampaksiring and (2) What are the implications of teacher chess learning in shaping student character at SMP Negeri 1 Tampaksiring? . The theories used in this research are Behavioristic Theory and Constructivism Theory. This research is qualitative research. The data collection methods in this research are by means of field observation, interviews, documentation and library techniques. Based on the results of qualitative data analysis, the implementation and implications of Catur Guru learning in shaping student character at SMP Negeri 1 Tampaksiring are considered effective, where this is implemented by school teachers in classroom learning. From the results of the analysis of the results obtained, it can be concluded that the implementation and implications of Catur Guru learning in shaping student character carried out by the school can be well received by students and is able to provide a significant improvement in the formation of student character.